Inside Back Cover: Double‐Strand DNA Breaks Induced by Paracyclophane Gold(I) Complexes (Chem. Eur. J. 26/2017). Issue 26 (20th March 2017) - Bestgen, Sebastian; Seidl, Carmen; Wiesner, Thomas; Zimmer, Andreas; Falk, Martina; Köberle, Beate; Austeri, Martina; Paradies, Jan; Bräse, Stefan; Schepers, Ute; Roesky, Peter W.
Abstract : Gold(I) complexes of ClickPhos [2.2]paracyclophane ligands were systematically studied with respect to their cytotoxic properties. Their efficiency in cytotoxicity was investigated in HeLa, MCF7 and HCT116 cells displaying different mechanisms of action, which involve apoptosis, necrosis, and DNA damage. The gold‐based cytostatics induce double‐strand DNA breaks (DSB) as shown by H2AX phosphorylation at foci of DSBs. More information can be found in the Full Paper by U. Schepers, P. W. Roesky et al. onpage 6315 ff.